2019
DOI: 10.1371/journal.ppat.1007881
|View full text |Cite
|
Sign up to set email alerts
|

Oxamniquine resistance alleles are widespread in Old World Schistosoma mansoni and predate drug deployment

Abstract: Do mutations required for adaptation occur de novo, or are they segregating within populations as standing genetic variation? This question is key to understanding adaptive change in nature, and has important practical consequences for the evolution of drug resistance. We provide evidence that alleles conferring resistance to oxamniquine (OXA), an antischistosomal drug, are widespread in natural parasite populations under minimal drug pressure and predate OXA deployment. OXA has been used since the 1970s to tr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 69 publications
1
36
0
Order By: Relevance
“…The phenotypic and genetic data from this setting suggest that natural variation in this schistosome population has some praziquantel resistance or tolerance (we could not differentiate these with our data). This is consistent with evidence of natural variation in resistance within schistosomes predating drug use to a former anti-schistosomal drug, oxaminiquine, where resistance alleles are known [58].…”
Section: Discussionsupporting
confidence: 83%
“…The phenotypic and genetic data from this setting suggest that natural variation in this schistosome population has some praziquantel resistance or tolerance (we could not differentiate these with our data). This is consistent with evidence of natural variation in resistance within schistosomes predating drug use to a former anti-schistosomal drug, oxaminiquine, where resistance alleles are known [58].…”
Section: Discussionsupporting
confidence: 83%
“…None of these SNPs affect Ca 2+ influx: they are therefore unlikely to have determined critical residues that determine binding between PZQ and Sm.TRPMPZQ (21). We examined the mutations present in Sm.TRPMPZQ in natural schistosome populations using exome sequencing from 259 miracidia, cercariae or adult parasites from 3 African countries (Senegal, Niger, Tanzania), the Middle East (Oman) and South America (Brazil) (51,52). We were able to sequence 36/41 exons of Sm.TRPMPZQ from 122/259 parasites on average (s.e.…”
Section: Chemical Blockers and Activators Of Smtrpmpzq Modulate Pzq-rmentioning
confidence: 99%
“…These findings also suggested that resistance to PZQ may be unlikely to establish or spread in these populations at the beginning of the national control program, given the current selection of targeting school-aged children alone. 69 Nevertheless, these studies on S. mansoni susceptibility to PZQ (at least within Uganda), as recent findings have shown for oxamniquine resistance, 66 have identified standing variation in drug efficacies and clearance rates on which selection can act. This might indeed be expected to accentuate as drug pressures over time increase.…”
Section: Introductionmentioning
confidence: 99%
“…The rate and likelihood of resistance developing is influenced by a broad range of factors including, but not exclusive to, baseline parasite genetic structure and underlying standing variation in drug tolerance on which selection can act, effective population size, refugia, and gene flow in parallel to treatment frequency, dosage, and whether single or combination drug regimens. 66 , 67 Figure 4 demonstrates how population genetics can, nevertheless, help evaluate and contribute to the detection of potential changes in drug resistance efficacy.…”
Section: Introductionmentioning
confidence: 99%